2020
DOI: 10.1016/j.neubiorev.2020.06.034
|View full text |Cite
|
Sign up to set email alerts
|

Are critical periods reversible in the adult brain? Insights on cortical specializations based on sensory deprivation studies

Abstract: We review here studies with visual and auditory deprived/recovery populations to argue for the need of a redefinition of the crucial role of unisensory-specific experiences during critical periods (CPs) on the emergence of sensory specializations. Specifically, we highlight that these studies, with emphasis on results with congenitally blind adults using visual sensory-substitution devices, consistently document that typical specializations (e.g., in visual cortex) could arise also in adulthood via other senso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 210 publications
(267 reference statements)
2
36
0
Order By: Relevance
“…Implementing multisensory training for blind individuals would have entailed the involvement of audio-tactile inputs, requiring an additional hardware component (i.e., to deliver tactile SSD stimulations), which both raises costs and is harder to adapt to an online platform as it would require constant maintenance. It is important though to note, that multisensory audio-visual approaches can potentially impact the rehabilitative aspects of visually impaired individuals, for instance, individuals with residual vision, or with degenerative visual loss (see for instance [ 49 , 50 ] suggesting the coupling of SSDs with sight restoration approaches). Our current results on the sighted population show that for this initial stage of SSD training, the unisensory and multisensory, perceptual and descriptive training methods were equally efficient.…”
Section: Discussionmentioning
confidence: 99%
“…Implementing multisensory training for blind individuals would have entailed the involvement of audio-tactile inputs, requiring an additional hardware component (i.e., to deliver tactile SSD stimulations), which both raises costs and is harder to adapt to an online platform as it would require constant maintenance. It is important though to note, that multisensory audio-visual approaches can potentially impact the rehabilitative aspects of visually impaired individuals, for instance, individuals with residual vision, or with degenerative visual loss (see for instance [ 49 , 50 ] suggesting the coupling of SSDs with sight restoration approaches). Our current results on the sighted population show that for this initial stage of SSD training, the unisensory and multisensory, perceptual and descriptive training methods were equally efficient.…”
Section: Discussionmentioning
confidence: 99%
“…One could therefore argue that once this critical period is over, the brain is less likely to adapt itself to a new condition. Nonetheless, a number of studies have reported neuroanatomical differences between CB and LB, and LB and subjects with normal vision, which challenges the rigidity of critical periods in the brain ( Heimler and Amedi, 2020 ). For example, cross-modal plastic processes have been usually found in CB whose visual cortex is activated by other senses like audition, touch and even smell [reviewed in Kupers and Ptito (2014) ].…”
Section: Sensory Substitution and Cross-modal Rewiring Of The Brain Imentioning
confidence: 99%
“…In contrast, our study provides novel evidence for metamodal engagement of intermediate auditory areas. This is particularly noteworthy given the sparse evidence for metamodal engagement of intermediate sensory areas (Heimler and Amedi, 2020). Studying metamodal engagement in intermediate sensory areas has been difficult because it is difficult to determine what cross-modal congruences might exist in a cognitive space – thereby highlighting the importance of focusing on congruences between neural codes when attempting cross-modal coupling of sensory processing hierarchies.…”
Section: Discussionmentioning
confidence: 99%